Growth and Yield Response of Coppiced Robusta Coffee to Application of Different Combinations of Nitrogen and Potassium - Sampson Konlan; Jerome Agbesi Dogbatse; Moses Kwame Aidoo; Diana Donkor Ntiamoah; Patricia Adu-Yeboah; Amos Kojo Quaye; Elliot Kwaku Anyidoho; Prince Pobee; Maame Adjoa Segbefia (International Journal of Agronomy)
Rejuvenation of coffee plants often requires coppicing of the trees, exposing the soil to forces of erosion and leaving the farmer without income for up to 2 years. This juvenile period is prolonged when the soil is depleted of nutrients such as nitrogen. A trial was therefore conducted on a coppiced Robusta coffee farm to evaluate the benefits of applying combinations of potassium and nitrogen to the soil during the rejuvenation period. The treatments evaluated were T1 (no fertilizer), T2 (200 kg N + 200 kg K), T3 (200 kg N + 300 kg N), T4 (200 kg N + 400 kg K), T5 (300 kg N + 200 kg K), T6 (300 kg N + 300 kg K), T7 (300 kg N + 400 kg K), T8 (400 kg N + 200 kg K), T9 (400 kg N + 300 kg K), and T10 (400 kg N + 400 kg K). These treatments were laid out in a randomized complete block design with three replications. Data collected included weed growth and composition, growth of the coffee plants, and berry production. The data were subjected to analysis of variance, and differences between treatment means were determined by the least significant differences at 5% probability. Results showed that the application of higher rates of N and K led to faster weed growth and accumulation of more weed dry matter. Higher rates (T9 & T10) led to the accumulation of higher levels of chlorophyll in coffee leaves. Application of T9 promoted stem diameter and height increase in the rejuvenated Robusta coffee, while a higher number of laterals were supported by the application of T7. The application of T4 and T9 promoted higher early yield in Robusta coffee. Cumulatively, except for T6, all the fertilizer treatments supported the production of higher clean coffee beans compared to the control and hence higher gross income from the sale coffee beans. Application of the T4 and T9 combinations supported higher cumulative increase in clean coffee yield, while application of T6 reduced the cumulative clean coffee yield relative to the control. It was, therefore, concluded that combinations of N and K should be applied to coffee plants during rejuvenation, with the 400 kg N + 300 kg K·ha−1 recommended for supporting faster regrowth, higher berry production, and gross income.